Global Dilemma and Needs Assessment Toward Achieving Sustainable Development Goals in Controlling Leishmaniasis - Mehdi Bamorovat; Iraj Sharifi; Ahmad Khosravi; Mohammad Reza Aflatoonian; Setareh Agha Kuchak Afshari; Ehsan Salarkia; Fatemeh Sharifi; Behnaz Aflatoonian; Faranak Gharachorloo; Ali Khamesipour; Mehdi Mohebali; Omid Zamani; et al. (Springer, 2024)
Abstract Leishmaniasis is a disease of poverty that imposes a devastating medical, social, and economic burden on over 1 billion people nationwide. To date, no in-depth study to analyze the major global challenges and needs assessment has been carried out. This investigation aimed to explore a comprehensive narrative review of leishmaniasis's main challenges and initially highlight obstacles that might impede the implementation of control measures. Also, we propose a specific list of priorities for needs assessment. The presence of socioeconomic factors, multiple clinical and epidemiological forms, various Leishmania species, the complexity of the life cycle, the absence of effective drugs and vaccines, and the lack of efficient vector and reservoir control make this organism unique and sophisticated in playing a tangled role to react tricky with its surrounding environments, despite extensive efforts and implementation of all-inclusive former control measures. These facts indicate that the previous strategic plans, financial support, and basic infrastructures connected to leishmaniasis surveillance are still insufficient. Strengthening the leishmaniasis framework in a context of accelerated programmatic action and intensification of cross-cutting activities along with other neglected tropical diseases (NTDs) is confidently expected to result in greater effectiveness, cost-benefit, and fruitful management. Sensitive diagnostics, effective therapeutics, and efficacious vaccines are vital to accelerating advancement toward elimination, and reducing morbidity/mortality and program costs. Collective actions devoted by all sectors and policy-makers can hopefully overcome technical and operational barriers to guarantee that effective and coordinated implementation plans are sustained to meet the road map for NTDs 2021- 2030 goals.